Soil Microbial Diversity and Network Organization Respond to Land Use and Agricultural Inputs Worldwide - Zaki Saati‐Santamaría; Sergio Pérez‐Gorjón; Daniel Abel‐Schaad; Alberto Acedo‐Bécares; Francisca Alba‐Sánchez; Amanda Lucia Alves; Weronika Babinska‐Wensierska; Jorge Ariel Marfetán; Carolina Barroetaveña; Kara Barry; Francisco Beitia; Katerina Biniari; et al. (Global Change Biology, 2026)
Soil microbiomes are critical for ecosystem functioning, yet the global influences of climate and agricultural practices on their diversity and structure remain incompletely characterized. Here we analyzed 1921 soil samples from 33 countries worldwide across diverse biomes to assess how climate gradients and agricultural inputs, including pesticides and fertilizers, shape prokaryotic and fungal communities. We found that microbial diversity peaks at intermediate temperatures and differs markedly between natural and agricultural soils, with agriculture increasing microbial diversity while altering community composition and ecological guilds. Pesticide use selectively reduced bacterial diversity and shifted fungal guilds, decreasing ectomycorrhizal fungi while increasing saprotrophs, whereas fertilization reduced microbial network cohesion, with organic and inorganic fertilizers eliciting distinct community responses. These findings reveal that climatic factors and agricultural management jointly influence soil microbial diversity, community structure, and network connectivity, with implications for soil health and ecosystem resilience in managed landscapes. Overall, our results demonstrate that agricultural practices, including the use of pesticides and both organic and inorganic fertilizers, act as strong ecological filters that reshape soil microbiomes worldwide—enhancing apparent diversity but driving a functional shift toward less mutualistic, more fragmented, and potentially less resilient communities.

Impact of climate change on freshwater macronutrients and agricultural yields across Britain - Nathan Missault; Victoria A. Bell; David M. Cooper; Ryan T. Sharp; Andrew P. Whitmore; Alice E. Milne; Helen N. Davies (Journal of Environmental Management, 2026)

IBIS: an Integrated Bayesian approach for unique Initial thorium corrections and age-depth models in U-Th dating of Speleothems - Christopher W. Kinsley; Jack N. Carter; Warren D. Sharp (Quaternary Science Reviews, 2025)

Downregulation of Fidgetin-Like 2 Increases Microglial Function: The Relationship Between Microtubules, Morphology, and Activity - Austin N. Smith; Alison Gregor; Lisa Baker; David J. Sharp; Kimberly R. Byrnes (Molecular Neurobiology, 2025)
The microtubule cytoskeleton regulates microglial morphology, motility, and effector functions. The microtubule-severing enzyme, fidgetin-like 2 (FL2), negatively regulates cell motility and nerve regeneration, making it a promising therapeutic target for central nervous system injury. Microglia perform important functions in response to inflammation and injury, but how FL2 affects microglia is unclear. In this study, we investigated the role of FL2 in microglial morphology and injury responses in vitro. We first determined that the pro-inflammatory stimulus, lipopolysaccharide (LPS), induced a dose- and time-dependent reduction in FL2 expression associated with reduced microglial ramification. We then administered nanoparticle-encapuslated FL2 siRNA to knockdown FL2 and assess microglial functions compared to negative control siRNA and vehicle controls. Time-lapse live-cell microscopy showed that FL2 knockdown increased the velocity of microglial motility. After incubation with fluorescently labeled IgG-opsonized beads, FL2 knockdown increased phagocytosis. Microglia were exposed to low-dose LPS after nanoparticle treatment to model injury-induced cytokine secretion. FL2 knockdown enhanced LPS-induced cytokine secretion of IL-1α, IL-1β, and TNFα. These results identify FL2 as a regulator of microglial morphology and suggest that FL2 can be targeted to increase or accelerate microglial injury responses. Graphical Abstract

Review of APSIM's soil nitrogen modelling capability for agricultural systems analyses - Kirsten Verburg; Heather R. Pasley; Jody S. Biggs; Iris Vogeler; Enli Wang; Henrike Mielenz; Val O. Snow; Chris J. Smith; Chiara Pasut; Andrea D. Basche; Di He; Sotirios V. Archontoulis; et al. (Agricultural Systems, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Perception of Body Fat and Body Fat Percentages Among Female College Students - M. Schmidt; D. Beeson; S. Keck; T. Pulver; M. Scott; N. Sharp; E. Weaver; C. Lyman; A. Grady (Journal of the Academy of Nutrition and Dietetics, 2024)

Physicochemical compatibility of caffeine citrate and caffeine base injections with parenteral medications used in neonatal intensive care settings - D. Thisuri N. De Silva; Michael Petrovski; Tobias Strunk; Nabeelah Mukadam; Madhu Page-Sharp; Brioni R. Moore; Kevin T. Batty (European Journal of Clinical Pharmacology, 2024)
Purpose To investigate the physicochemical compatibility of caffeine citrate and caffeine base injections with 43 secondary intravenous (IV) drugs used in Neonatal Intensive Care Unit (NICU) settings. Methods Caffeine citrate (20 mg/mL or 10 mg/mL) or caffeine base injection (10 mg/mL) were mixed in a volume ratio of 1:1 with the secondary drug solution to simulate Y-site co-administration procedures in NICUs. Physical compatibility was evaluated based on visual observation for 2 h, against a black and white background and under polarised light, for changes in colour, precipitation, haze and evolution of gas. Chemical compatibility was determined from caffeine concentration measurements, using a validated high-performance liquid chromatography assay. Results Six of the 43 secondary drugs tested (aciclovir, amphotericin (liposomal), furosemide, hydrocortisone, ibuprofen and ibuprofen lysine) were physically incompatible with caffeine citrate undiluted injection (20 mg/mL), at their high-end, clinically relevant concentrations for NICU settings. However, when tested at lower concentrations, hydrocortisone (1 mg/mL) was physicochemically compatible, whereas furosemide (0.2 mg/mL) was physically incompatible with caffeine citrate. The six drugs which showed physical incompatibility with caffeine citrate 20 mg/mL injection were also physically incompatible with caffeine citrate 10 mg/mL solution. All 43 secondary drugs tested were physicochemically compatible with caffeine base injection. Conclusions Most secondary test drugs, except aciclovir, amphotericin (liposomal), furosemide, hydrocortisone, ibuprofen and ibuprofen lysine, were physicochemically compatible with caffeine citrate injection. Caffeine base injection was physicochemically compatible with all 43 test drugs tested.

Geological and anthropogenic contributions of metal(loid)s in the artisanal and small-scale mining-impacted Ocoña watershed of Arequipa, Peru - Isaac J.P. Simon; Katharina Pfaff; Alexis Navarre-Sitchler; Jorge Crespo; Elizabeth Holley; Gary Vanzin; Madeleine N. Guillen Gomez; Sergio Ticona-Corrales; Jonathan O. Sharp (Applied Geochemistry, 2024)

The mobility of the brachycephalic canine nostril in relation to the degree of nostril stenosis - C.A.T. Sharp; N.-C. Liu; A. Guy; J.F. Ladlow (The Veterinary Journal, 2024)

Top ten priorities for global saltmarsh restoration, conservation and ecosystem service research - Julien Pétillon; Emma McKinley; Meghan Alexander; Janine B. Adams; Christine Angelini; Thorsten Balke; John N. Griffin; Tjeerd Bouma; Sally Hacker; Qiang He; Marc J.S. Hensel; Carles Ibáñez; et al. (Science of The Total Environment, 2023)

Continuous home cage monitoring of activity and sleep in mice during repeated paroxetine treatment and discontinuation - Helen M. Collins; Raquel Pinacho; S. K. Eric Tam; Trevor Sharp; David M. Bannerman; Stuart N. Peirson (Psychopharmacology, 2023)
Rationale Non-invasive home cage monitoring is emerging as a valuable tool to assess the effects of experimental interventions on mouse behaviour. A field in which these techniques may prove useful is the study of repeated selective serotonin reuptake inhibitor (SSRI) treatment and discontinuation. SSRI discontinuation syndrome is an under-researched condition that includes the emergence of sleep disturbances following treatment cessation. Objectives We used passive infrared (PIR) monitoring to investigate changes in activity, sleep, and circadian rhythms during repeated treatment with the SSRI paroxetine and its discontinuation in mice. Methods Male mice received paroxetine (10 mg/kg/day, s.c. ) for 12 days, then were swapped to saline injections for a 13 day discontinuation period and compared to mice that received saline injections throughout. Mice were continuously tracked using the Continuous Open Mouse Phenotyping of Activity and Sleep Status (COMPASS) system. Results Repeated paroxetine treatment reduced activity and increased behaviourally-defined sleep in the dark phase. These effects recovered to saline-control levels within 24 h of paroxetine cessation, yet there was also evidence of a lengthening of sleep bouts in the dark phase for up to a week following discontinuation. Conclusions This study provides the first example of how continuous non-invasive home cage monitoring can be used to detect objective behavioural changes in activity and sleep during and after drug treatment in mice. These data suggest that effects of paroxetine administration reversed soon after its discontinuation but identified an emergent change in sleep bout duration, which could be used as a biomarker in future preclinical studies to prevent or minimise SSRI discontinuation symptoms.

Correction: Long-chain omega-3 polyunsaturated fatty acids decrease mammary tumor growth, multiorgan metastasis and enhance survival - Saraswoti Khadge; Geoffrey M. Thiele; John Graham Sharp; Timothy R. McGuire; Lynell W. Klassen; Paul N. Black; Concetta C. DiRusso; Leah Cook; James E. Talmadge (Clinical & Experimental Metastasis, 2023)

What's the crux? Falcon nesting closures and rock climbing constraints at Harpers Ferry National Historical Park - Michala L. Hendrick; Chris A.B. Zajchowski; Jessica P. Fefer; Ryan L. Sharp; Chandler Berry; James N. Maples; Eddie L. Hill (Journal of Outdoor Recreation and Tourism, 2023)

The role of trade in pacific food security and nutrition - T.D. Brewer; N.L. Andrew; D. Abbott; R. Detenamo; E.N. Faaola; P.V. Gounder; N. Lal; K. Lui; A. Ravuvu; D. Sapalojang; M.K. Sharp; R.J. Sulu; et al. (Global Food Security, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: Histamine, mast cell tryptase and post-exercise hypotension in healthy and collapsed marathon runners - I. T. Parsons; M. J. Stacey; L. Faconti; N. Hill; J. O’Hara; E. Walter; B. Farukh; R. McNally; H. Sharp; A. Patten; R. Grimaldi; N. Gall; et al. (European Journal of Applied Physiology, 2021)

Histamine, mast cell tryptase and post-exercise hypotension in healthy and collapsed marathon runners - I. T. Parsons; M. J. Stacey; L. Faconti; N. Hill; J. O’Hara; E. Walter; B. Farukh; R. McNally; H. Sharp; A. Patten; R. Grimaldi; N. Gall; et al. (European Journal of Applied Physiology, 2021)
Purpose Heat stress exacerbates post-exercise hypotension (PEH) and cardiovascular disturbances from elevated body temperature may contribute to exertion-related incapacity. Mast cell degranulation and muscle mass are possible modifiers, though these hypotheses lack practical evidence. This study had three aims: (1) to characterise pre–post-responses in histamine and mast cell tryptase (MCT), (2) to investigate relationships between whole body muscle mass (WBMM) and changes in blood pressure post-marathon, (3) to identify any differences in incapacitated runners. Methods 24 recreational runners were recruited and successfully completed the 2019 Brighton Marathon (COMPLETION). WBMM was measured at baseline. A further eight participants were recruited from incapacitated runners (COLLAPSE). Histamine, MCT, blood pressure, heart rate, body temperature and echocardiographic measures were taken before and after exercise (COMPLETION) and upon incapacitation (COLLAPSE). Results In completion, MCT increased by nearly 50% from baseline ( p = 0.0049), whereas histamine and body temperature did not vary ( p > 0.946). Systolic (SBP), diastolic (DBP) and mean (MAP) arterial blood pressures and systemic vascular resistance (SVR) declined ( p < 0.019). WBMM negatively correlated with $$Δ $$ Δ SBP ( r = − 0.43, p = 0.046). For collapse versus completion, there were significant elevations in MCT (1.77 ± 0.25 μg/L vs 1.18 ± 0.43 μg/L, p = 0.001) and body temperature (39.8 ± 1.3 °C vs 36.2 ± 0.8 °C, p < 0.0001) with a non-significant rise in histamine (9.6 ± 17.9 μg/L vs 13.7 ± 33.9 μg/L, p = 0.107) and significantly lower MAP, DBP and SVR ( p < 0.033). Conclusion These data support the hypothesis that mast cell degranulation is a vasodilatory mechanism underlying PEH and exercise associated collapse. The magnitude of PEH is inversely proportional to the muscle mass and enhanced by concomitant body heating.

Localized Impacts of Hurricane Irma on Diadema antillarum and Coral Reef Community Structure - Julia N. Kobelt; William C. Sharp; Travis N. Miles; Colette J. Feehan (Estuaries and Coasts, 2020)

Reference points for predators will progress ecosystem‐based management of fisheries - Simeon L. Hill; Jefferson Hinke; Sophie Bertrand; Lowell Fritz; Robert W. Furness; James N. Ianelli; Matthew Murphy; Ricardo Oliveros‐Ramos; Lorien Pichegru; Rowland Sharp; Richard A. Stillman; Peter J. Wright; et al. (Fish and Fisheries, 2020)
Ecosystem‐based management of fisheries aims to allow sustainable use of fished stocks while keeping impacts upon ecosystems within safe ecological limits. Both the FAO Code of Conduct for Responsible Fisheries and the Aichi Biodiversity Targets promote these aims. We evaluate implementation of ecosystem‐based management in six case‐study fisheries in which potential indirect impacts upon bird or mammal predators of fished stocks are well publicized and well studied. In particular, we consider the components needed to enable management strategies to respond to information from predator monitoring. Although such information is available in all case‐studies, only one has a reference point defining safe ecological limits for predators and none has a method to adjust fishing activities in response to estimates of the state of the predator population. Reference points for predators have been developed outside the fisheries management context, but adoption by fisheries managers is hindered a lack of clarity about management objectives and uncertainty about how fishing affects predator dynamics. This also hinders the development of adjustment methods because these generally require information on the state of ecosystem variables relative to reference points. Nonetheless, most of the case‐studies include precautionary measures to limit impacts on predators. These measures are not used tactically and therefore risk excessive restrictions on sustainable use. Adoption of predator reference points to inform tactical adjustment of precautionary measures would be an appropriate next step towards ecosystem‐based management.

Larval influx of Diadema antillarum to the Florida Keys linked to passage of a Tortugas Eddy - Colette J. Feehan; William C. Sharp; Travis N. Miles; Michael S. Brown; Diane K. Adams (Coral Reefs, 2019)

Long-chain omega-3 polyunsaturated fatty acids decrease mammary tumor growth, multiorgan metastasis and enhance survival - Saraswoti Khadge; Geoffrey M. Thiele; John Graham Sharp; Timothy R. McGuire; Lynell W. Klassen; Paul N. Black; Concetta C. DiRusso; Leah Cook; James E. Talmadge (Clinical & Experimental Metastasis, 2018)

Assessing uncertainties in crop and pasture ensemble model simulations of productivity and N 2 O emissions - Fiona Ehrhardt; Jean‐François Soussana; Gianni Bellocchi; Peter Grace; Russel McAuliffe; Sylvie Recous; Renáta Sándor; Pete Smith; Val Snow; Massimiliano de Antoni Migliorati; Bruno Basso; Arti Bhatia; et al. (Global Change Biology, 2018)
Simulation models are extensively used to predict agricultural productivity and greenhouse gas emissions. However, the uncertainties of (reduced) model ensemble simulations have not been assessed systematically for variables affecting food security and climate change mitigation, within multi‐species agricultural contexts. We report an international model comparison and benchmarking exercise, showing the potential of multi‐model ensembles to predict productivity and nitrous oxide (N 2 O) emissions for wheat, maize, rice and temperate grasslands. Using a multi‐stage modelling protocol, from blind simulations (stage 1) to partial (stages 2–4) and full calibration (stage 5), 24 process‐based biogeochemical models were assessed individually or as an ensemble against long‐term experimental data from four temperate grassland and five arable crop rotation sites spanning four continents. Comparisons were performed by reference to the experimental uncertainties of observed yields and N 2 O emissions. Results showed that across sites and crop/grassland types, 23%–40% of the uncalibrated individual models were within two standard deviations ( SD ) of observed yields, while 42 (rice) to 96% (grasslands) of the models were within 1 SD of observed N 2 O emissions. At stage 1, ensembles formed by the three lowest prediction model errors predicted both yields and N 2 O emissions within experimental uncertainties for 44% and 33% of the crop and grassland growth cycles, respectively. Partial model calibration (stages 2–4) markedly reduced prediction errors of the full model ensemble E‐median for crop grain yields (from 36% at stage 1 down to 4% on average) and grassland productivity (from 44% to 27%) and to a lesser and more variable extent for N 2 O emissions. Yield‐scaled N 2 O emissions (N 2 O emissions divided by crop yields) were ranked accurately by three‐model ensembles across crop species and field sites. The potential of using process‐based model ensembles to predict jointly productivity and N 2 O emissions at field scale is discussed.

Pharmacological evidence that 5-HT2C receptor blockade selectively improves decision making when rewards are paired with audiovisual cues in a rat gambling task - Wendy K. Adams; Chris Barkus; Jacqueline-Marie N. Ferland; Trevor Sharp; Catharine A. Winstanley (Psychopharmacology, 2017)

Molecular variability and phylogenetic relationships of guava (Psidium guajava L.) cultivars using inter-primer binding site (iPBS) and microsatellite (SSR) markers - A. Mehmood; S. Luo; N. M. Ahmad; C. Dong; T. Mahmood; Y. Sajjad; M. J. Jaskani; P. Sharp (Genetic Resources and Crop Evolution, 2016)

Fornix deep brain stimulation enhances acetylcholine levels in the hippocampus - Sarah Hescham; Ali Jahanshahi; Judith V. Schweimer; Stephen N. Mitchell; Guy Carter; Arjan Blokland; Trevor Sharp; Yasin Temel (Brain Structure and Function, 2016)

Overexpression of AtDREB1D transcription factor improves drought tolerance in soybean - Satish K. Guttikonda; Babu Valliyodan; Anjanasree K. Neelakandan; Lam-Son Phan Tran; Rajesh Kumar; Truyen N. Quach; Priyamvada Voothuluru; Juan J. Gutierrez-Gonzalez; Donavan L. Aldrich; Stephen G. Pallardy; Robert E. Sharp; Tuan-Hua David Ho; et al. (Molecular Biology Reports, 2014)

Assessing the sensitivity of habitats to fishing: from seabed maps to sensitivity maps a - N. C. Eno; C. L. J. Frid; K. Hall; K. Ramsay; R. A. M. Sharp; D. P. Brazier; S. Hearn; K. M. Dernie; K. A. Robinson; O. A. L. Paramor; L. A. Robinson (Journal of Fish Biology, 2013)
In the Welsh part of the Irish Sea, a method was developed for assessing the sensitivity of different seabed habitats to existing fishing activities, across a range of potential fishing intensities. The resistance of 31 habitats and their associated biological assemblage to damage by 14 categories of fishing activity were assessed along with the rate at which each habitat would recover following impact (resilience). Sensitivity was scored based on a combination of the resistance of a habitat to damage and its subsequent rate of recovery. The assessments were based, wherever possible, on scientific literature, with expert judgement used to extrapolate results to habitat and gear combinations not directly examined in the published literature. The resulting sensitivity matrices were then subject to further peer review at a series of workshops. Following consensus on the habitat sensitivity, these data were combined with the most resolved sea‐floor habitat maps. These habitat sensitivity maps can help inform the development of site‐specific management plans, as well as having a place in spatial planning and aiding managers in developing dialogue with other stakeholders. A case study of their application is provided.

CDER Risk Assessment Exercise to Evaluate Potential Risks from the Use of Nanomaterials in Drug Products - Celia N. Cruz; Katherine M. Tyner; Lydia Velazquez; Kenneth C. Hyams; Abigail Jacobs; Arthur B. Shaw; Wenlei Jiang; Robert Lionberger; Peter Hinderling; Yoon Kong; Paul C. Brown; Tapash Ghosh; et al. (The AAPS Journal, 2013)

Evaluation of PRDM9 variation as a risk factor for recurrent genomic disorders and chromosomal non-disjunction - Christelle Borel; Fanny Cheung; Helen Stewart; David A. Koolen; Christopher Phillips; N. Simon Thomas; Patricia A. Jacobs; Stephan Eliez; Andrew J. Sharp (Human Genetics, 2012)

Shrub-Steppe Early Succession Following Juniper Cutting and Prescribed Fire - Jonathan D. Bates; Kirk W. Davies; Robert N. Sharp (Environmental Management, 2011)

Intra-uterine growth restriction is associated with increased apoptosis and altered expression of proteins in the p53 pathway in villous trophoblast - Alexander E. P. Heazell; Andrew N. Sharp; Philip N. Baker; Ian P. Crocker (Apoptosis, 2011)

Correlations Between Gene Expression and Mercury Levels in Blood of Boys With and Without Autism - Boryana Stamova; Peter G. Green; Yingfang Tian; Irva Hertz-Picciotto; Isaac N. Pessah; Robin Hansen; Xiaowei Yang; Jennifer Teng; Jeffrey P. Gregg; Paul Ashwood; Judy Van de Water; Frank R. Sharp (Neurotoxicity Research, 2011)

Correlations of Gene Expression with Blood Lead Levels in Children with Autism Compared to Typically Developing Controls - Yingfang Tian; Peter G. Green; Boryana Stamova; Irva Hertz-Picciotto; Isaac N. Pessah; Robin Hansen; Xiaowei Yang; Jeffrey P. Gregg; Paul Ashwood; Glen Jickling; Judy Van de Water; Frank R. Sharp (Neurotoxicity Research, 2011)

The effect of 48 weeks of aerobic exercise training on cutaneous vasodilator function in post-menopausal females - Gary J. Hodges; Lisa Sharp; Claire Stephenson; Ashish Y. Patwala; Keith P. George; David F. Goldspink; N. Tim Cable (European Journal of Applied Physiology, 2010)

The Environmental Polymorphisms Registry: a DNA resource to study genetic susceptibility loci - Patricia C. Chulada; Heather L. Vahdat; Richard R. Sharp; Tracy C. DeLozier; Paul B. Watkins; Susan N. Pusek; Perry J. Blackshear (Human Genetics, 2008)

Plant–pollinator interactions in a Mexican Acacia community - Nigel E. Raine; Alice Sharp Pierson; Graham N. Stone (Arthropod-Plant Interactions, 2007)

Air-sea Coupling During the Tropical Cyclones in the Indian Ocean: A Case Study Using Satellite Observations - Bulusu Subrahmanyam; V. S. N. Murty; Ryan. J. Sharp; James. J. O’Brien (Pure and Applied Geophysics, 2005)

Nuclear BAG-1 expression inhibits apoptosis in colorectal adenoma-derived epithelial cells - J. D. Barnes; N. J. Arhel; S. S. Lee; A. Sharp; M. Al-Okail; G. Packham; A. Hague; C. Paraskeva; A. C. Williams (Apoptosis, 2005)

Construction and characterisation of a hexaploid wheat (Triticum aestivum L.) BAC library from the reference germplasm ‘Chinese Spring’ - S. Allouis; G. Moore; A. Bellec; R. Sharp; P. Faivre Rampant; K. Mortimer; S. Pateyron; T. N. Foote; S. Griffiths; M. Caboche; B. Chalhoub (Cereal Research Communications, 2003)

Metazoan parasites of yellowtail kingfish, Seriola lalandi lalandi , in New Zealand: Prevalence, intensity, and site preference - N. J. Sharp; C. W. Poortenaar; B. K. Diggles; T. J. Willis (New Zealand Journal of Marine and Freshwater Research, 2003)
The prevalence and intensity of metazoan ectoparasites on the skin and gills of kingfish, Seriola lalandi lalandi (Carangidae), collected from White Island (n = 32), Ranfurly Banks (n = 7), and Three Kings Islands (n = 7), is reported. Kingfish were host to two monogenean and four copepod ectoparasite species, Benedenia seriolae, Zeuxapta seriolae, Caligus lalandei, Caligus aesopus, Neobrachiella spp., and Lernanthropus spp., respectively. B. seriolae and C. lalandei infect the skin, whereas the remaining parasites were located on the gills. All parasites exhibited considerable variability in the prevalence and intensity of infection. A few kingfish were completely devoid of C. aesopus, Neobrachiella spp., and/or Lernanthropus spp., whereas others were infected by moderate numbers of these species. However, all kingfish were infected by B. seriolae and Z. seriolae . Therefore, it appears that acclimation of wild kingfish from the east coast of New Zealand's North Island into captivity will lead to the transfer of both B. seriolae and Z. seriolae , and that effective quarantine measures will be required to avoid introducing these parasites into broodstock systems. The site preferences of B. seriolae, Z. seriolae , and C. aesopus were also investigated. B. seriolae exhibited a preference for attachment on the lateral surfaces of the skin behind the dorsal fin, but forward of the anal fin. Z. seriolae displayed a preference for attachment on gill arches 2 and 3, particularly in gill filaments located in the upper regions of the buccal cavity. C. aesopus most commonly occurred on the gill arch.

Characterisation of Triticum vavilovii-derived stripe rust resistance using genetic, cytogenetic and molecular analyses and its marker-assisted selection - H. S. Bariana; G. N. Brown; N. U. Ahmed; S. Khatkar; R. L. Conner; C. R. Wellings; S. Haley; P. J. Sharp; A. Laroche (Theoretical and Applied Genetics, 2002)

Poster Session - J. van S. Graver; H. J. Banks; A. K. Sharp; A. Contessi; N. Baldassari; M. Maggioli; Sabine Prozell; Ch. Reichmuth; Maria Otília Carvalho; Ana Paula Pereira; A. Mexia; Sylvia Allen; et al. (Phytoparasitica, 2001)

Xp deletions associated with autism in three females - N. S. Thomas; Andrew J. Sharp; Caroline E. Browne; David Skuse; Chris Hardie; Nicholas R. Dennis (Human Genetics, 1999)

Does erythrocyte infusion improve 3.2-km run performance at high altitude? - Kent B. Pandolf; Andrew J. Young; Michael N. Sawka; James L. Kenney; Mark W. Sharp; Randy R. Cote; Beau J. Freund; C. Robert Valeri (European Journal of Applied Physiology, 1998)

A study of females with deletions of the short arm of the X chromosome - Rowena S. James; Brian Coppin; Paola Dalton; Nicholas R. Dennis; Caroline Mitchell; Andrew J. Sharp; David H. Skuse; N. Simon Thomas; P. A. Jacobs (Human Genetics, 1998)

Influenza infection in humans and pigs in southeastern China - N. Zhou; S. He; T. Zhang; W. Zou; L. Shu; G. B. Sharp; R. G. Webster (Archives of Virology, 1996)

Monoclonal antibodies for the identification of herpesvirus simiae (B virus) - L. M. Cropper; D. N. Lees; R. Patt; I. R. Sharp; D. Brown (Archives of Virology, 1992)

A novel method for regenerating the protoplasts of thermophilic bacilli - R. M. Dunn; M. J. Munster; R. J. Sharp; B. N. Dancer (Archives of Microbiology, 1987)